Sustainability of nature-based tourism - Törn, A. (Anne) (University of Oulu, 2007)
Abstract Nature-based tourism has increased considerably during recent years, which has raised questions about the tolerance of ecosystems experiencing growing visitor numbers. The present thesis focuses on the ecological and social sustainability of nature-based tourism in protected areas and their surroundings. The objective of the ecological studies was to determine the effects of tourism on vegetation, soils and risk of introduction of alien plant species. The social survey investigated whether opinions concerning nature conservation and tourism by local people are dependent on socio-economic and demographic factors. The studies were carried out in Oulanka and Pallas-Ounastunturi National Parks, and in the Ruka and Syöte regions, in northern Finland. This research demonstrated that nature-based tourism (hiking, horse-riding and skiing) affected boreal forests, altering vegetation, soils and trail networks. The major effects were; reduction in vegetation cover, including of different life-forms, changes in plant species composition, soil chemistry and soil erosion. Trampling decreased plant cover more on slopes compared to flat terrain. Moreover, downward trampling reduced the plant cover more than did upward trampling. In addition, horse riding resulted in the introduction and establishment of a range of alien plant species. In general, ecological changes due to nature-based tourism were inevitable even when there were limited numbers of visitors. Respondents to the survey were classified into three groups according to their opinions concerning nature conservation and tourism development: (i) supporters of nature conservation, (ii) critical to nature conservation and (iii) critical to tourism development. The majority of respondents were supporters of nature conservation. However, opinions were strongly dependent on the socio-demographic background of the respondents, such as residential area, age, level of education and indigenousness. Since the impacts of tourism were dependent on the characteristics of ...